Positive impact of the participation in the ENCHANTED trial in reducing Door-to-Needle Time. Issue 1 (December 2017) - Yang, Jie; Wang, Xia; Yu, Jian; Hang, Jing; Lavados, Pablo; Robinson, Thompson; Arima, Hisatomi; Lindley, Richard; Anderson, Craig; Chalmers, John
Abstract Door-to-needle time (DNT) is a key performance indicator for efficient use of intravenous thrombolysis in acute ischemic stroke (AIS). We aimed to determine whether DNT improved over time in the Enhanced Control of Hypertension and Acute Stroke Study (ENCHANTED) and the clinical predictors of DNT. Temporal trends in DNT were assessed across fourths of time since activation of study centers using generalized linear model. Predictors of long DNT (>60 min) were determined in logistic regression models. Overall mean DNT (min) was 71.8 (95% confidence interval [CI] 70.4–73.2), but decreased significantly over time (fourths): 77.9 (74.9–80.9), 69.3 (66.7–72.0), 69.1 (66.5–71.8) and 71.4 (68.7–74.2) (P for trend, 0.003). The reduction in DNT was particularly marked in China (P for trend, 0.001), but was not significant across the other participating countries (P for trend, 0.065). Independent predictors of long DNT were recruitment from China, short onset-to-door time, lower numbers of patients treated per center, higher diastolic blood pressure, off-hour admission, and absence of proximal clot occlusion. DNT in ENCHANTED declined progressively during the trial, especially in China. However, DNT in China is still longer than the key performance parameter of ≤60 minutes recommended in guidelines. Effective national programs are needed to improve DNT in China.